2010
DOI: 10.1038/embor.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of zinc‐finger domain of Nanos and its functional implications

Abstract: Nanos is an RNA-binding protein that is involved in the development and maintenance of germ cells. In combination with Pumilio, Nanos binds to the 3 0 untranslated region of a messenger RNA and represses its translation. Nanos has two conserved Cys-Cys-His-Cys zinc-finger motifs that are indispensable for its function. In this study, we have determined the crystal structure of the zinc-finger domain of zebrafish Nanos, for the first time revealing that Nanos adopts a novel zinc-finger structure. In addition, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…For example, the UGU motif of the PRE is recognized by repeats R8 through R6. This high-resolution structure, combined with previous crystal structures of Drosophila Pum (Edwards et al, 2001) and zebrafish Nos ZFs (Hashimoto et al, 2010), allowed us to build and refine the ternary complex model.
10.7554/eLife.17096.007Figure 2.Nanos embraces Pumilio and hb RNA to stabilize the ternary complex.( A ) Crystal structure of a Drosophila Nos-Pum- hb NRE2 RNA ternary complex. Pum is shown as a ribbon diagram (yellow), Nos is shown as a surface representation (blue) and hb NRE2 RNA is shown as a stick model colored by atom type.
…”
Section: Resultsmentioning
confidence: 99%
“…For example, the UGU motif of the PRE is recognized by repeats R8 through R6. This high-resolution structure, combined with previous crystal structures of Drosophila Pum (Edwards et al, 2001) and zebrafish Nos ZFs (Hashimoto et al, 2010), allowed us to build and refine the ternary complex model.
10.7554/eLife.17096.007Figure 2.Nanos embraces Pumilio and hb RNA to stabilize the ternary complex.( A ) Crystal structure of a Drosophila Nos-Pum- hb NRE2 RNA ternary complex. Pum is shown as a ribbon diagram (yellow), Nos is shown as a surface representation (blue) and hb NRE2 RNA is shown as a stick model colored by atom type.
…”
Section: Resultsmentioning
confidence: 99%
“…3). Nanos-family members are distinguished throughout the animal kingdom by a conserved CCHC Zinc-finger motif that is required for RNA binding (Hashimoto et al, 2010). Alone, Nanos has little RNA-sequence-specific binding activity, but in all species studied it acts as a translational repressor (reviewed in Lai & King, 2013; Lai, Zhou, Luo, Fox, & King, 2011).…”
Section: Mechanisms For Protecting the Germline During The Mztmentioning
confidence: 99%
“…This zinc-finger domain was crystallized for the first time using the zebrafish Nanos (Hashimoto et al, 2010), which revealed that its basic surface is directly involved in RNA binding. In contrast to Nanos, its binding partner protein, Pumilio, is not limited to the germ line and instead is uniformly distributed e.g.…”
Section: Introductionmentioning
confidence: 99%